A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus - Sankaran, Pradeep M.; Caleb, John T.D.; Sebastian, Pothalil A. (European Journal of Taxonomy, 2020)
Indian spider species currently assigned to Storena Walckenaer, 1805 are revised mostly based on the type material available in the National Zoological Collection, Zoological Survey of India, Kolkata. A new genus, Laminion gen. nov. is proposed to include four species; three are transferred from Storena: Laminion arakuensis (Patel & Reddy, 1989) gen. et comb. nov., Laminion birenifer (Gravely, 1921) gen. et comb. nov. and Laminion debasrae (Biswas & Biswas, 1992) gen. et comb. nov., whereas the fourth species is from Suffasia Jocqué, 1991: Laminion gujaratensis (Tikader & Patel, 1975) gen. et comb. nov. The species Storena tikaderi Patel & Reddy, 1989 syn. nov. is synonymised with L. birenifer gen. et comb. nov. Storena dibangensis Biswas & Biswas, 2006 and Storena indica Tikader & Patel, 1975 are transferred to Mallinella Strand, 1906. All the type material examined are imaged and redescribed. In addition, images of the type material of Storenomorpha joyaus (Tikader, 1970) are presented.